2017
DOI: 10.1177/0969733016646156
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in action-oriented research in Indonesia

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Thus, the government, represented by the Ministry of Higher Education should put more effort into implementing research ethics guidelines in Jordanian academic and research institutions. This might improve the degree of standardization of research ethics in the country, similar to that reported in other developing countries [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 72%
“…Thus, the government, represented by the Ministry of Higher Education should put more effort into implementing research ethics guidelines in Jordanian academic and research institutions. This might improve the degree of standardization of research ethics in the country, similar to that reported in other developing countries [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 72%
“…The lack of awareness on this matter could result in practices susceptible to ethical violations due to the lack of knowledge among local researchers, the lack of information access for international researchers conducting research in Indonesia, as reported by Rachmawaty (2017). If needed, as a part of the efforts to promote awareness, the government could also require all governmentfunded studies (through the mechanisms of grants or scholarships) to enclose proof of ethical clearance.…”
Section: Rekomendasi Untuk Pemerintahmentioning
confidence: 99%
“…Diperlukan sosialisasi yang sistematis dengan melibatkan universitas dan lembaga penelitian untuk memastikan proses etik diterapkan sebagai bagian dari tanggung jawab pemerintah dalam melindungi warga negaranya. Kurangnya sosialisasi tentang hal ini membuka peluang terjadinya praktik yang sangat rentan terhadap pelanggaran etika akibat minimalnya pengetahuan peneliti lokal, serta kurang teraksesnya informasi bagi peneliti internasional dalam melakukan penelitian di Indonesia, seperti yang dilaporkan Rachmawaty (2017). Jika diperlukan, sebagai bagian dari sosialisasi, pemerintah juga dapat mewajibkan seluruh penelitian yang disponsori oleh pemerintah (melalui mekanisme hibah penelitian atau beasiswa) untuk menyertakan bukti uji lolos etik.…”
Section: Rekomendasi Untuk Pemerintahunclassified
“…This problem emerged as Indonesian academics remain highly dependent on external parties in producing scientific knowledge and innovation output like international peer-review journals (Lakitan, Hidayat, & Herlinda, 2012), patents, and other intellectual properties. In addition, multiple problems in managing complex foreign research permit, ethical clearance, protection of intellectual property rights international collaboration on related subjects involved human-being have remarkably engendered a stagnated innovation in Indonesia and would hamper the national science and technological development in year to come (Rachmawaty, 2017;Shetty et al, 2014).…”
Section: The Current State Of Innovation In Indonesiamentioning
confidence: 99%